The double movement in Africa: a Nkrumah-Polanyi analysis of free market fatigue in Ghana’s private sector - Langan, Mark (Review of International Political Economy, 2021)
Karl Polanyi’s double movement is a key tool for conceptualising free market fatigue in African business communities wrought by the insecurities of trade liberalisation. Synthesising Polanyi with Kwame Nkrumah’s work on neo-colonialism, the article argues that exhausted business communities in Africa can contest free market reforms and push for a return to developmentalist strategies, underscoring a double movement. In this discussion it highlights Ghana, a ‘donor darling’ in terms of historical implementation of free market reform. It builds upon the author’s engagement with 66 interviewees – business people and policy stakeholders – in relation to the condition of that country’s poultry and tomato industries. Unpacking interviewee narratives, the article points to a striking common theme, namely that business stakeholders call for the re-embedding of the economy via developmentalist strategies to move beyond neo-colonial trade systems. In this vein, the article provides an original contribution to studies of International Political Economy by demonstrating the efficacy of a Nkrumah-Polanyi ensemble for making sense of business communities’ potential role in countermovements for developmentalism in Africa.
Political Science
Keywords: Ghana; Nkrumah; Polanyi; double movement; free trade; neo-colonialism; private sector

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Area Studies; Anthropology
Keywords: countermovement; populism; visegrad countries

Seeing like a Socialist: On Socialist Worldviews from Polanyi to Taylor to Now - Grant, John; Dunlop, Mallory (New Political Science, 2021)
In this article we argue that reinvigorating socialist politics requires championing a socialist worldview that goes beyond the critique of capitalism. Neglecting such an outlook leaves socialism tethered to the fortunes of capitalism and inhibits a broader account of its own virtues. We begin by explaining why worldview thinking is appropriate today. Then we examine two underappreciated works by Karl Polanyi (his 1927 lecture “On Freedom”) and Charles Taylor (his 1974 essay “Socialism and Weltanschauung”). Each treats worldview thinking as indispensable and we use them as catalysts for developing a socialist vision. Finally, we bring our insights to bear on the worldview potential of socialist republicanism. We contend that a promising worldview emerges by elaborating the following components: a political anthropology of human possibilities; anti-capitalism, social freedom, and non-domination; socialist civic virtues; and the promise and limits of pluralism.
Publisher: Routledge _eprint: https://doi.org/10.1080/07393148.2021.2002093
Keywords: TAYLOR; Charles; socialism

The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism - Pfeiffer, Sabine (International Critical Thought, 2021)
This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation. Polanyi analyzed the development of “self-regulating” markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a “greater” transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.
Sociology
Keywords: digital capitalism; digital transformation; distribution; political economy; productive forces

Karl Polanyi, the New Deal and the Green New Deal - Dale, Gareth (Environmental Values, 2021)
In this paper, I present an analysis of those aspects of Karl Polanyi's social and political thought that relate to environmentalism and 'green' politics today. I discuss whether or not he prefigured the degrowth movement, before focusing on his understanding of the New Deal (1933-1939). At the time of writing, the prospect appears likely of a return, at a global scale, of economic slump, mass unemployment and ecological crisis, the background conditions to which Franklin D. Roosevelt's New Deal was responding on the national scale. The paper concludes by drawing lessons from this comparison for possible Green New Deals.
Keywords: Green New Deal; Karl Polanyi; New Deal; degrowth; embeddedness

On Polanyi - Munck, Ronaldo (Area Development and Policy, 2021)
Karl Polanyi provides a rich repertoire of concepts to build a critical understanding of the world of globalization and alternatives to the status quo. In reviewing two recent collections around the work of Polanyi, we show some of the concepts that might be developed in terms of ‘using Polanyi’. This would include his inspired double-movement concept and the way he dealt with non-capitalist societies. Polanyi is as relevant for the so-called developing societies as he is for the advanced industrial societies where he has garnered most attention.
Publisher: Routledge _eprint: https://doi.org/10.1080/23792949.2020.1830708
Keywords: Polanyi; double movement; globalización; globalization; movimiento doble; no capitalista; non-capitalist; Поланьи; глобализация; двойное движение; некапиталистический.; 全球化; 双重运动; 波兰尼; 非资本主义

Karl Polanyi and the Reappraisal of Happiness Economics - Özveren, Eyüp; Gürpinar, Erkan; Karagöz, Ufuk (Journal of Economic Issues, 2021)
Happiness economics unearths the undesirable effects of economic growth and criticizes the economic model based on the belief in the supremacy of market relations over the relational bonds of society. Economic growth brings about substantial increases in material well-being; yet, it has the potential to destroy the social and environmental fabric of society. This is visible in the post-World War II cross-country variability of the subjective well-being measures, which shows the importance of relational goods and associational activities. These themes echo Karl Polanyi’s concerns over the destructive effects of the self-regulating market mechanism. In this paper, we demonstrate the relevance of the interdisciplinary work of Polanyi for happiness economics. We argue that Polanyi’s conception of the self-regulating market system comes together with the spread of unhappiness. The treatment of labor as a fictitious commodity is of utmost significance in this respect. No less important is the similar degrading of land, a proxy for environment. Furthermore, the distinction Polanyi maintained between “exploitation” and “cultural degeneration” in assessing the Industrial Revolution is useful for this critique. In essence, Polanyi’s approach is relevant to explain the deterioration of social relations, which is thought to be the ultimate reason behind the happiness paradox.
Economics
Keywords: Karl Polanyi; consumption; happiness; hedonism; self-regulating market system

MERCADOS E PRAÇAS DE MERCADO: KARL POLANYI E O CAPITALISMO CONTEMPORÂNEO - Parpet, Marie France Garcia (Sociologia & Antropologia, 2021)
Resumo Explorando as distinções conceituais entre mercado, sistema de mercados formadores de preço e praça de mercado, concebidas por Karl Polanyi, o artigo mostra a pertinência dessas diferenças para a análise do capitalismo contemporâneo, ao focalizar a caracterização e os efeitos específicos de praças de mercado da atualidade. Evoca a contribuição de Polanyi para repensar o conceito de mercado tal como referido na literatura econômica e especificar a historicidade dos mercados, sobretudo do sistema de mercados formadores de preço (equivalente de sistema capitalista), opondo esses conceitos a praças de mercado. Recorre a trabalhos etnográficos e/ou sociológicos, sobre praças de mercado contemporâneas, verificando que elas existem nas configurações atuais das trocas mercantis e podem criar valor simbólico e material, estando na origem de processos de diferenciação social, intensificados, por exemplo, no caso das plataformas digitais.
Sociology; Anthropology
Keywords: Karl Polanyi; Mercado; institucionalização; plataformas digitais.; praça de mercado; salões de exposição; sistema de mercados

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Sociology; Anthropology
Keywords: DALE; Gareth; Karl Polanyi; capitalism; democracy; market

The unfinished development of the frontier: a Karl Polanyi reading of the conflict between the forestry industry, Mapuche communities and the Chilean State - Undurraga, Tomás; Márquez, Felipe (Sociologia & Antropologia, 2021)
Resumo O artigo explora conflitos entre a indústria florestal, as comunidades Mapuche e o Estado chileno à luz da leitura de Polanyi sobre a expansão capitalista. Oferece análise histórico-institucional das maneiras pelas quais o Estado chileno usou a florestação para domar uma fronteira selvagem e os povos nativos que ali vivem. Argumenta que o aumento da violência nessa zona responde à crescente militarização do Estado na área e reflete o contramovimento de proteção social iniciado pelo povo Mapuche - contra uma indústria florestal de livre mercado que transformou a paisagem, limitando o acesso dos Mapuche a terras e florestas, e contra um processo de modernização liderado pelo Estado chileno que corroeu as instituições tradicionais dos Mapuche e lhes ofereceu integração em termos desiguais, como “campesinos pobres”.
Anthropology; Sociology
Keywords: Chile; Estado chileno; Mapuche; Polanyi; contramovimento; countermovement; forest industry; indústria florestal; proteção social; social protection

New Limits of the Neoliberalism: Society and Market - Vidal, Laura; Correa, Eugenia (Journal of Economic Issues, 2021)
Neoliberalism has been able to change the markets and the economy of societies around the world. These transformations are especially important with regards to fictitious commodities: land, labor, and money. However, the 2020 pandemic imposes new limits, when life itself is at risk globally. This work highlights the major neoliberal reforms relating to fictitious commodities, the difficulties of society to resist and create counterweights. The health crisis that has emerged with the COVID-19 pandemic is the result of decades of over-exploitation of nature and human beings. The reforms over fictitious commodities, especially labor, have led to a constant and systematic decline of society. This article is supported by the theoretical legacy of Karl Polanyi and Kari Polanyi Levitt that allows us to consider the most important trends of neoliberal reforms and their main objectives.
Economics
Keywords: fictitious commodities; health crisis; neoliberal counterrevolution; neoliberalism

Non-market institutions and crime in US counties: Hayek v. Polanyi - Zullo, Roland (Review of Social Economy, 2021)
Karl Polanyi’s The great transformation emphasized the importance of non-market institutions for social equity and stability. In that same era, Friedrich Hayek postulated in The road to serfdom that superior economies were market-based and featured minimal government. I compare these worldviews in relation to property and violent crime. Using US county data, change in crime is modeled as a function of economic structure, economic conditions, and demographics. Consistent with Polanyi, the size of the public sector in the economy negatively associates with crime. Within the public sector, education is a critical crime-reducing function, more so than law enforcement. Industry diversity is positively associated with crime, contrary to Hayek. Manufacturing equates with lower crime and the size of the private non-profit sector is unrelated to crime. Overall the results favor Polanyi’s assertion that non-market institutions are necessary to counter the harsh outcomes arising from market economic systems.
Publisher: Routledge _eprint: https://doi.org/10.1080/00346764.2019.1663909
Keywords: H41 (public goods); P17 (capitalism performance); Socialism; Z13 (economic sociology); crime; laissez-faire; non-market institutions; public goods

On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Sociology
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory

Our Obsolete Marketing Mentality: George Fisk, Meet Karl Polanyi - Benton, Raymond (Journal of Macromarketing, 2021)
Marketing in general can have greater influence if a new, yet old, perspective on marketing is adopted—something akin to the original orientation of marketing. Adopting George Fisk’s definition of marketing and marrying it with notions derived from the institutional economist Karl Polanyi is proposed. The histories of marketing thought and of institutional economics are reviewed to demonstrate their affinity and similar origins. Fisk’s conceptualization of marketing as societies’ provisioning systems is shown to correspond with Polanyi’s conceptualization of economies as instituted processes, admitting more than the market and the state as ways economies have historically and cross-culturally integrated with society. The obsolete marketing mentality is that marketers, including macromarketers, are overly fixated on the market and ignore or overlook alternatives. The Fisk/Polanyi orientation will attract macromarketers interested in marketing and development, critical marketing, sustainability, alternative economies, and those interested in the long-term prospects of macromarketing. Adopting this old, but new, framework will connect the past with the future, permit macromarketers make a mark on a larger intellectual landscape and serve to invite scholars in this larger landscape to engage with macromarketing.
Publisher: SAGE Publications Inc
Keywords: Future of Macromarketing; George Fisk; German Historical School; History of Economic Thought; Institutional Economics; Karl Polanyi; Marketing and Economics; history of marketing thought; macromarketing

Instituições Sociais e Sistema Econômico: a perspectiva de Karl Polanyi - Freitas, Tales Rabelo (Revista da Sociedade Brasileira de Economia Política, 2021)
For Karl Polanyi, the economic system cannot be analyzed in isolation from social institutions. The economicism fallacy neglects social variables that are fundamental for determining economic action and systemic transformations. This implies that the rise of the self-regulated market system and its dominance over social institutions are not a natural movement when analyzed in the light of the entire history of human societies. For the author, what happened was a kind of uprooting of the economy, although this movement has been supported in a very specific institutional context in the past, and with no possibility of sustainability. As the economy is a by-product of social institutions, the Polanyian approach understands that any analysis, whether of economic dynamics or its transformations, must be carried out taking into account the needs of society as a whole.
Sociology; Political Science
Keywords: Karl Polanyi; economicismo; economism; instituições; institutions

Wirtschaftsethik der ›always embedded market economy‹. Überlegungen zu einer Idee von Polanyi - Haase, Michaela (Zeitschrift für Wirtschafts- und Unternehmensethik, 2021)
Capitalism is a social relation that cannot be reduced to the characteristics associated with it - markets, private property, profit and profit orientation. This relation can be shaped in different ways. The article refers to Karl Polanyi’s idea of the ›always embedded market economy‹ in order to develop basic characteristics of an example of post-capitalist economic ethics. Alternate abstract: Der Kapitalismus ist ein soziales Verhältnis, das sich nicht auf die mit ihm in Verbindung gebrachten Merkmale - Märkte, Privateigentum, Gewinn- und Profitorientierung - reduzieren lässt. Dieses Verhältnis kann auf verschiedene Weise ausgestaltet werden. Der Beitrag referiert auf die Idee der ›always embedded market economy‹ von Karl Polanyi, um Grundzüge einer postkapitalistischen Wirtschaftsethik zu entwickeln.
Economics; Philosophy
Keywords: business and economics; capitalism; ethics; market economies; philosophy; private property

Fascism and the enduring problem of the liberal individual in Polanyi - Millett, Kris (Dewey Studies, 2021)
This application of Polanyi to the question of fascism’s resurgence provides an important corrective to mainstream liberal explanations (e.g., Albright 2018), inviting the reader to “look up rather than down” (Lim 2021) by tying fascism’s significance to the functioning of the capitalist system rather than to the personalities of fascist politicians or their degree of mass support. The merits of this notwithstanding, I argue that current Polanyian treatments have neglected to engage with a core aspect of Polanyi’s theory, which is that fascism, at its roots, is a fundamentally anti-individualist ideology that aims to address a moral and social crisis of the individual subject in liberal capitalism. Omitting this risks obfuscating what makes fascism distinctive as well as why its ideas have retained their appeal.
Sociology
Keywords: essence of fascism; fascism; individualism

ТРАДИЦИОННАЯ РЫНОЧНАЯ ЭКОНОМИКА И ЕЁ АНТИЦИКЛИЧЕСКИЙ ПОТЕНЦИАЛ В ОЦЕНКАХ ИССЛЕДОВАТЕЛЕЙ XIX-XX ВЕКОВ - Анатольевич, Орлянский Евгений (Наука о человеке: гуманитарные исследования, 2021)
The article deals with the first stage of the market economic system - the traditional market economy. The traditional market economy is considered in the assessment of its main researchers. The main goal of the study is to identify the main characteristics and features of the traditional economy, which would explain the absence of pronounced cyclical elements in it. It is assumed that several essential elements of such an economy carry the strongest countercyclical potential. The article uses the methodology of comparative analysis, which will help to find common ground among the most famous researchers of the traditional market economy. The study of the traditional market economic system was carried out in the context of overcoming the stereotype of the closed development of economic processes and the impossibility of influencing them by non-economic factors. This is confirmed by the fact that most of the countercyclical elements of the traditional market economy are derived from the spiritual and ethical sphere. At the same time, an integral part of the article is the position that this economic system retains all the characteristic features of a market economy. The traditional market economy practically did not experience cyclical tendencies in its development. This was due to the fact that this economic system contained built-in elements that ensured the absence in the traditional economy of both cyclicality itself and periodic cyclical crises.
Economics